2007
DOI: 10.1002/msc.104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of ocular manifestations of RA: is there a need for routine screening?

Abstract: Visual impairment does not appear to be particularly prevalent in RA, obviating the need for a screening programme. Utilization of the VFQ-25 as a screening tool in RA requires further consideration. The high prevalence of cataracts in participants on steroids emphasizes the need to prescribe the minimum required dose. The high prevalence of dry eyes suggests that a Schirmer's test should be performed regularly, with prescription of artificial tears if required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It is possible that a low‐grade inflammatory process, due to the presence of auto‐antibodies for lacrimal tissue, impairs adequate tear production. Asymptomatic dry eyes have been noted with high prevalence in other systemic inflammatory diseases such as rheumatoid arthritis 17. In our IBD patients with dry eyes, just under half had symptoms, so routine questions about eye symptoms would only detect a minority of patients in the GI office.…”
Section: Discussionmentioning
confidence: 85%
“…It is possible that a low‐grade inflammatory process, due to the presence of auto‐antibodies for lacrimal tissue, impairs adequate tear production. Asymptomatic dry eyes have been noted with high prevalence in other systemic inflammatory diseases such as rheumatoid arthritis 17. In our IBD patients with dry eyes, just under half had symptoms, so routine questions about eye symptoms would only detect a minority of patients in the GI office.…”
Section: Discussionmentioning
confidence: 85%
“…Sicca symptoms were also common in this study. Piper et al found decreased lacrimal flow in 70.7% of the RA patients attending a screening clinic (18).…”
Section: Introductionmentioning
confidence: 99%
“…Severe aqueous tear deficiency leading to keratoconjunctivitis sicca (KCS) is assumed to be rare in childhood. Sjögren’s syndrome (SS) with symptoms of dry eyes and dry mouth is seldom seen in children: the prevalence is assumed to be about 5% in juvenile rheumatic diseases 35…”
Section: Introductionmentioning
confidence: 99%